Architecture Development of Information System of an Enterprise - Dotsenko, S. I.; Kamenskyi, S. S. (Systems and Technologies, 2019)
In the paper the analysis of methods of modeling of activity of the enterprise is carried out. It is shown that at present there is no single commonly accepted method for modeling the activity of an enterprise. And this, in turn, prevents the development of a single tool for its simulation. This circumstance follows from the initial position of the theory and practice of enterprise modeling and business processes, namely, the process approach to the presentation of the activity. The method of establishing unambiguous correspondence (likeness) of architectures of the functional, organizational and infor-mation representations of the enter-prise is proposed.